2016
DOI: 10.3390/polym8070255
|View full text |Cite
|
Sign up to set email alerts
|

Microfibrillated Lignocellulose Enables the Suspension-Polymerisation of Unsaturated Polyester Resin for Novel Composite Applications

Abstract: Abstract:A new route towards embedding fibrillated cellulose in a non-polar thermoset matrix without any use of organic solvent or chemical surface modification is presented. It is shown that microfibrillated lignocellulose made from cellulose with high residual lignin content is capable of stabilising an emulsion of unsaturated polyester resin in water due to its amphiphilic surface-chemical character. Upon polymerisation of the resin, thermoset microspheres embedded in a microfibrillated cellulose network ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 36 publications
0
14
0
Order By: Relevance
“…Transparent nanocellulose/polystyrene nanocomposite films were prepared by hot-pressing treatment after polymerization (Figure 7 ) [ 74 ] using a surface-carboxylated nanocellulose prepared by TEMPO-mediated oxidation as a stabilizer. The mechanical properties were comparable with those of a nanocellulose/polystyrene nanocomposite prepared by solvent casting and drying of nanocellulose/polystyrene mixture in N,N -dimethylformamide [ 99 ]. Using this process, finely organized nanocellulose/poly(methyl methacrylate) [ 100 ] and nano-fibrillated chitin/acrylic resin [ 101 ] composites were prepared.…”
Section: Applicationsmentioning
confidence: 88%
“…Transparent nanocellulose/polystyrene nanocomposite films were prepared by hot-pressing treatment after polymerization (Figure 7 ) [ 74 ] using a surface-carboxylated nanocellulose prepared by TEMPO-mediated oxidation as a stabilizer. The mechanical properties were comparable with those of a nanocellulose/polystyrene nanocomposite prepared by solvent casting and drying of nanocellulose/polystyrene mixture in N,N -dimethylformamide [ 99 ]. Using this process, finely organized nanocellulose/poly(methyl methacrylate) [ 100 ] and nano-fibrillated chitin/acrylic resin [ 101 ] composites were prepared.…”
Section: Applicationsmentioning
confidence: 88%
“…It is suggested that this denser and less porous structure of MFLC specimens is caused by the wetting and infiltration of cellulose fibrils by FA, providing a significant reinforcement effect upon in situ polymerisation. Considering the furanic ring structure present in FA, wetting of lignin-containing microfibrillated cellulose, which was shown to provide considerably improved miscibility with non-polar solvents and polymers compared to MFC produced from bleached pulp (Ballner et al 2016;Herzele et al 2016;Winter et al 2017;Yan et al 2016), seems highly plausible for furfuryl alcohol. Apart from better wetting and interpenetration, the FA monomer may also directly react with lignin units found in MFLC according to reaction 2 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…With a crystallinity index of 0.70 for MFC and 0.74 for MFLC, both cellulose materials used show similar crystallinity (Winter et al 2017). The choice of these two fibril variants was motivated by their repeatedly observed differences in surface-chemical properties, with MFLC being essentially less polar than MFC (Ballner et al 2016;Herzele et al 2016;Winter et al 2017;Yan et al 2016). Aqueous fibril slurries were adjusted to a solid content of 4 wt%.…”
Section: Preparation Of Porous Materialsmentioning
confidence: 99%
“…In the present study, a CNF-stabilized monomer-inwater emulsion was used as a starting point to design a CNF/polymer composite structure [21]. Several studies on polymer composite preparation through Pickering emulsions have been reported, where nanocelluloses [22,23], microfibrillated lignocellulose [24], or chitin nanofibrils [25][26][27] were used as stabilizers. Furthermore, we report the synthesis of core-shell microparticles using this Pickering emulsion as a template [28].…”
Section: Introductionmentioning
confidence: 99%